ANALISIS KEPUASAN WISATAWAN DOMESTIK PADA ATRAKSI DOLPHIN DI PANTAI LOVINA, BULELENG - Ayu Antari, Kadek; Suardana, I Wayan; Dewi, LGLK. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 1 (2020): Jurnal IPTA (July 2020), 2020)
Lovina beach is known for the dolphin attraction. Watching dolphin attraction, tourists were transported by boat. As a provider, the helmsman tried to give the best of service to the tourists. However, there were various views of both positive and negative opinions from tourists regarding the services rendered during used. Thus, it must be known to be the dosmetic tourist satisfaction using boat service at Lovina Beach. Data collected by the method of observation, interviews, questionnaires, documentation and literature study. Determination of the sample using purposive sampling technique. Data analysis techniques using customer satisfaction index and importance performance analysis in the form of a Cartesius diagram. The results show that the level of tourist expectation is 4.28 which means it is in the very important category. Furthermore, the value of the captain's performance level obtained a value of 3.77 which was categorized as good. Calculation of the gap value shows the gap between the level of expectation and the level of performance with the acquisition of a value of -0.51. Analysis of the level of tourist satisfaction based on the calculation of the customer satisfaction index shows that tourists are satisfied with a value of 75.54%. There are 4 indicators that need to be prioritized to be improved, including the availability of life jackets, responsibility for the safety of tourists, a sense of security while using a boat and the helmsman has the ability to create good relationships with tourists.